Domain-Specific Inter-textual Non-Taxonomic Extraction (DSINTE) - Nur Fatin Nabila Mohd Rafei Heng; Nurlida Basir; Madihah Mohd Saudi; Mamat, A; Azmi-Murad, MA; Mustapha, N; Deris, MM (IEEE, 2024)
Indexed by WOS/ Scopus